Serum levels of soluble CD163 as a specific marker of macrophage/monocyte activity in sarcoidosis patients - Tanimura, Hirotsugu; Mizuno, Kana; Okamoto, Hiroyuki (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: Monocyte-macrophage lineage cells are the main immunocompetent cells in sarcoidosis. The main cellular elements of sarcoidal granulomas are epithelioid cells and multinucleated giant cells (MGC). MGC are also produced in vitro by human blood monocytes following various stimuli. The in vitro formation of MGC is a useful tool for understanding granulomas. CD163, a scavenger receptor for the hemoglobin-haptoglobin complex, is expressed on monocytes/macrophages and shed into blood in a soluble form (sCD163) after stimulation from Toll-like receptors and oxidative stress. sCD163 serum levels have been reported to increase in inflammatory or infectious conditions. Objective: The aim of the present study was to examine the relationship between serum levels of sCD163 and the conventional disease markers of sarcoidosis, and also to evaluate sCD163 levels in culture supernatants following the formation of MGC by human peripheral monocytes in vitro. Patients and methods: Twenty sarcoidosis patients and twenty healthy subjects were enrolled in the study. sCD163 serum levels were evaluated using sCD163 ELISA. MGC were formed from peripheral blood monocytes by treatment with supernatant of concanavalin A-stimulated peripheral blood mononuclear cells, and sCD163 levels in the culture supernatants were measured by ELISA. Results: sCD163 serum levels were significantly higher in sarcoidosis patients than in healthy controls and correlated with ACE and soluble interleukin-2 receptor serum levels. sCD163 levels in culture supernatants increased with the production of MGC. Conclusions: sCD163 may be used as a favorable specific marker of macrophage/monocyte activity in order to more clearly understand the disease activity of sarcoidosis. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 99-105)